2021
DOI: 10.1039/d0mh01759k
|View full text |Cite
|
Sign up to set email alerts
|

Threshold switching memristor-based stochastic neurons for probabilistic computing

Abstract: Stochastic neurons based on CuS/GeSe conductive bridge threshold switching memristors are designed to mimic the probabilistic computing ability of the brain at a hardware level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…As depicted in Figure 4F, tuning the input pulse width can generate stochastic outputs with different firing rates. Another implementation of a Cu filament-based TS device (Wang et al, 2021) presented LIF neuron behavior by coupling the device with two resistors in series and a capacitor in parallel (Figure 4G). The capacitor imitates the membrane potential, whereas the resistors limit the total current intensity and divide the input voltage.…”
Section: Filament-based Neuronmentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Figure 4F, tuning the input pulse width can generate stochastic outputs with different firing rates. Another implementation of a Cu filament-based TS device (Wang et al, 2021) presented LIF neuron behavior by coupling the device with two resistors in series and a capacitor in parallel (Figure 4G). The capacitor imitates the membrane potential, whereas the resistors limit the total current intensity and divide the input voltage.…”
Section: Filament-based Neuronmentioning
confidence: 99%
“…(H) Measured stochastic spike events of the CuS/GeSe-based neuronal circuit. (I) Comparison of the output probability of deterministic and stochastic neurons(Wang et al, 2021).…”
mentioning
confidence: 99%
“…The dynamic properties of FLBP-CsPbBr 3 TSM were investigated in Fig. 2d by applying the voltage pulses and recording the resulting current [39][40][41][42][43] . Following the applied voltage pulses of 1 V, the current jumped suddenly to Icc of 1 × 10 −5 A.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that V hold (~1.2 V) is more stable than V th (~3.1 V) of the Ag/V 2 C/W memristor. Still, there is a window between V th and V hold , which shows potential for neuromorphic circuits design [43,44].…”
Section: Resultsmentioning
confidence: 99%